Reversible Tuning of Extrinsic 3D Chirality in Chalcogenide NonChiral Metasurfaces. Issue 8 (12th February 2023) - Cao, Tun; Mao, Libang; Fan, Hangwei; Lian, Meng; Jia, Jingyuan; Su, Ying; Ren, Haonan
Abstract: The chiroptical response occurring in the chiral metamaterials (MMs) has crucial and extensive applications for stereochemistry, polarization optics, and spintronics. Yet, such intrinsically chiral metamaterials are restricted to a complicated subwavelength chiral profile, causing pronounced fabrication challenges, particularly at the near‐infrared (N‐IR) spectral regime. Instead, extrinsic chirality can also be observed in the nonchiral MMs under an oblique incidence, indicating that the chiroptical response can be achieved with simple structures. The development of photon‐spin selective integrated devices needs an actively reversible tuning of chirality in MMs. Herein, a reversible switching of the extrinsic chirality at the N‐IR region is demonstrated by integrating a nonvolatile chalcogenide semiconductor, Ge2 Sb2 Te5, into the nonchiral MMs design. It provides an ultrafast and reconfigurable tuning of transmittance circular dichroism (TCD) between amorphous and crystalline states under a stimulus of a nanosecond pulsed laser at a wavelength of 532 nm. Meanwhile, it also effectively manipulates the TCD by titling both rotation and incident angles while fixing geometrical parameters. Utilizing ellipsometry and analytical inversion, it can obtain not only linear but circular birefringence‐dichroism pairs from a single general ellipsometry measurement, which gives a comprehensive description of the polarization characteristics of the non‐chiral MMs, having an advantage over the typical circular dichroism measurements. Abstract : A reversible switching of the extrinsic chirality at the near‐infrared region is demonstrated by integrating a nonvolatile chalcogenide semiconductor, Ge2 Sb2 Te5, into the nonchiral MMs design. It provides an ultrafast and reconfigurable tuning of transmittance circular dichroism between amorphous and crystalline states under a stimulus of nanosecond pulsed laser at a wavelength of 532 nm.